Formação continuada de professores dos anos iniciais do ensino fundamental: estudo em uma escola municipal do assentamento favela, Mossoró – RN - Silva, Elizeni Belo da (Universidade Federal Rural do Semi-Árido, 2019)
The present study has as its central theme the Continuing Training of Teachers from the early years of elementary school of basic education of the field. We point out as a general objective "to understand how the continued training of teachers of the beginning years of elementary school of the Municipal School Francisco Ferreira Souto, Favela Settlement, Mossoró - RN" develops. Regarding the specific objectives, we highlight (1) to highlight how the continuing training of teachers from the initial years of elementary school of the Francisco Ferreira Souto Municipal School, Favela Settlement, Mossoró - RN develops; (2) identify contributions from the continuing education of teachers from the early years of elementary school to teaching work at the Francisco Ferreira Souto Municipal School, Favela Settlement, Mossoró - RN; and (3) describe limits on the continuing training of teachers in the early years of elementary school of the Francisco Ferreira Souto Municipal School, Favela Settlement, Mossoró - RN. In methodological parameters, we recorded that the research was done under the qualitative approach, is typified as an exploratory and descriptive study and used as a data collection technique the questionnaire consisting of 10 (ten) open questions. The locus of the study confers on the Francisco Ferreira Souto Municipal School, located in the Favela Settlement, Mossoró - RN. In the study subjects, two professors participated, who teach in multiserial classes from the 1st to the 5th year of elementary school. We conclude that the continuing training of teachers, research participants, is important for the development of teaching work in the school context, but does not generally provide a link with Field Education, since it is developed from topics that do not directly guide The Field Education. We emphasize that one of the limits emphasized by teachers, derived from continuing education, gives the time to reconcile teaching work at school and the training actions they experience/experience.
Monografia
Keywords: Formação continuada de professores; Educação básica; Educação do campo; Continuing teacher training; Basic education; Education of the field; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO RURAL